Research Method for Exploring Discourse on the Rights for Religion for Transgender - Rr. Siti Kurnia Widiastuti (UIN Sunan Kalijaga Yogyakarta, 2017)
This paper explores several research methods used by researchers and published in various scientific journals to examine transgender issues in various countries. Transgender individuals are one of the gender-based minorities in social life. They live in uncomfortable conditions. They face life’s problems, which include problems in expressing religious rights, economic stability, and getting professional jobs. Like other human beings, they also have the right as citizens. These rights include civil rights, including religious rights, political rights, and social rights. There are several research methodologies that may be appropriate to be applied in research on transgender-related issues, namely life history, ethnography, phenomenology, feminist approach, textual or hermeneutic interpretation, and case studies.[Tulisan ini mengeksplorasi beberapa metode penelitian yang digunakan oleh para peneliti yang dipublikasikan dalam berbagai jurnal ilmiah untuk meneliti isu-isu transgender di berbagai negara. Para individu transgender merupakan salah satu kelompok minoritas berdasarkan gender di dalam kehidupan bermasyarakat. Mereka hidup dalam kondisi yang tidak nyaman. Mereka menghadapi berbagai problem kehidupan, yang termasuk di dalamnya adalah problem dalam mengekspresikan hak beragama, stabilitas ekonomi, dan mendapatkan pekerjaan profesional. Sebagaimana layaknya manusia lainnya, mereka juga memiliki hak sebagai warga negara. Hak tersebut antara lain adalah hak sipil yang termasuk di dalamnya hak beragama, hak berpolitik, dan hak bersosial. Ada beberapa metodologi penelitian yang mungkin sesuai untuk diterapkan dalam penelitian pada isu-isu yang berkaitan dengan transgender, yaitu sejarah hidup (life history), etnografi, fenomenologi, pendekatan feminis, interpretasi teks atau hermeneutik, dan studi kasus.](This article is based on a preliminary of Dissertation that is written by Rr. Siti Kurnia Widiastuti for an Inter-Religious Study (IRS), Universitas Gadjah Mada, Yogyakarta, Indonesia.)